1993
DOI: 10.1038/361072a0
|View full text |Cite
|
Sign up to set email alerts
|

A gene for the mouse pink-eyed dilution locus and for human type II oculocutaneous albinism

Abstract: The mouse pink-eyed dilution (p) locus on chromosome 7 is associated with defects of skin, eye and coat pigmentation. Mutations at p cause a reduction of eumelanin (black-brown) pigment and altered morphology of black pigment granules (eumelanosomes), but have little effect on pheomelanin (yellow-red) pigment. We show here that the human complementary DNA DN10, linked to the p locus in mice, identifies the human homologue (P) of the mouse p gene, and appears to encode an integral membrane transporter protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
257
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(267 citation statements)
references
References 23 publications
9
257
1
Order By: Relevance
“…The locus for the P gene which is implicated in type II oculocutaneous albinism also lies within this region. 77 Recent studies have shown that AS deletion patients with hypopigmentation frequently have a mutation of the P gene on the remaining chromosomal homologue 78 79 and some patients have the characteristic ocular findings of albinism with misrouting of optic nerve fibres at the optic chiasm. 80 Patients with uniparental disomy of chromosome 15 have a low incidence of seizures, microcephaly, and hypopigmentation.…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…The locus for the P gene which is implicated in type II oculocutaneous albinism also lies within this region. 77 Recent studies have shown that AS deletion patients with hypopigmentation frequently have a mutation of the P gene on the remaining chromosomal homologue 78 79 and some patients have the characteristic ocular findings of albinism with misrouting of optic nerve fibres at the optic chiasm. 80 Patients with uniparental disomy of chromosome 15 have a low incidence of seizures, microcephaly, and hypopigmentation.…”
Section: Genetic Counsellingmentioning
confidence: 99%
“…9 However, the highest incidence of OCA2 so far molecularly characterized at slightly o1:2000 is in the Native American Navajos with a carrier frequency of 4.5%, estimated to originate from a single founder. 10 The OCA2 locus maps to chromosome 15q11.2-q12 11 and is the human homolog of the mouse pink-eyed dilution gene (p) 12,13 encoding the P-protein. Structurally, the 838 amino-acid P-protein is predicted to contain 12 transmembrane-spanning domains.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to oculocutaneous albinism type 1, which results from Tyr mutations, patients with OCA2 express active TYR (King et al, 1985). p was initially thought to be a melanosomal tyrosine transporter (Kugelman and Van Scott, 1968;Rinchik et al, 1993;Lee et al, 1995;Sviderskaya et al, 1997;Rosemblat et al, 1998). However, kinetic studies of tyrosine uptake showed that there was a functional tyrosine transporter system in melanosomes of p-null melanocytes, and no difference in the rate of tyrosine uptake was found between wild-type and p-null melanocytes (Gahl et al, 1995;Potterf et al, 1998).…”
Section: Introductionmentioning
confidence: 99%